Composite hollow fiber membrane dehumidification: A review on membrane module, moisture permeability and self-cleaning performance. (December 2021) - Zhao, Wenjun; Lu, Hao; Li, Chaosheng
Highlights: The heat and mass transfer performance of HFM module with different structures were reviewed. Optimization of moisture permeability and self-cleaning modification for HFM were reviewed. The research gap and future research direction on HFM dehumidification were discussed. Abstract: Hollow fiber membrane (HFM) module has a wide range of applications in different areas of the separation technology because of its high packing density and selective permeability. However, it is easy to cause the fouling of the membrane surface as the moist air will carry dust particles into membrane-based dehumidification processes. The membrane surface fouling may greatly reduce the performance of the humidification/dehumidification efficiency of membrane module. At present, the main problems that limit the HFM dehumidification technology are the lack of membrane permeability and membrane surface pollution. In this paper, the moisture permeability process of membrane module and the surface modification of the membrane were reviewed. It was found that the heat and mass transfer performance of HFM module will be affected by the shape and arrangement of the fiber membrane tube as well as the flow pattern between the air and the solution. The surface modification can further improve the moisture permeability of the membrane, while the superhydrophobic modification can improve the self-cleaning ability of membrane surface and resist the pollution of dust particles.